Lemon (Citrus limon) leaf alkaloid-rich extracts ameliorate cognitive and memory deficits in scopolamine-induced amnesic rats - Olubukola H. Oyeniran; Opeyemi-Paul I. Omotosho; Iyanuoluwa I. Ademola; Omodele Ibraheem; Onyinyechi R. Nwagwe; Chinemelum A. Onodugo (Elsevier, 2024)
Introduction: Lemon (Citrus limon) leaf, an excellent Traditional Chinese Medicine (TCM), called li meng in TCM, is known to contain several bioactive compounds that could mitigate oxidative stress and boost memory. Hippocampus, a critical brain region, is deeply intertwined with memory formation and learning processes. Amnesia is a prominent category of cognitive impairment characterized by memory loss. There is no scientific data on the effects of lemon leaf alkaloid-rich extract (LLAE) in animal models. Hence, this study evaluated the effects of LLAE from lemon on neurobehavioural parameters, cholinergic, monoaminergic, and purinergic enzyme activities, and oxidative stress biomarkers in the hippocampus of scopolamine-induced amnesic rats. Methods: Alkaloid was extracted from lemon leaf using standard method. Experimental rats were treated with 100 mg/kg and 200 mg/kg LLAE and 5 mg/kg donepezil (standard drug) for fourteen days prior to memory impairment induced by a single administration of intraperitoneal injection of 1 mg/kg scopolamine. The experimental design included eight groups, encompassing four groups of non-amnesic rats and four groups of amnesic rats respectively. Results: Cognitive and memory assessments, employing Morris water maze, Y-maze and open field maze tests, revealed significant (p < 0.05) lowered spatial memory and exploratory behaviours in scopolamine-induced amnesic rats. Moreover, a significant (p < 0.05) negative modulation of neuronal enzyme activities and oxidative stress biomarkers was observed in the hippocampus of scopolamine-induced amnesic rats. Conversely, treatment with LLAE exhibited a pronounced attenuation of these alterations. Histopathological assessments of the hippocampus also confirm these changes. Conclusion: These findings underscore the potential therapeutic efficacy of LLAE in mitigating cognitive and memory deficits in the hippocampus of scopolamine-induced amnesic rats. Hence, LLAE could be considered as a potent natural alternative in management of neurodegenerative disorders, particularly amnesia.